Konsentrasi Sukrosa Dan Agar Di Dalam Media Pelestarian In-Vitro Ubi Jalar Var. Sukuh - Jane K. J Laisina (Faculty of Agriculture, Pattimura University, 2013)
The objective of this research was to obtain suitable concentration of sucrose and agar in the sweet potato (Ipomea batatas (L) Lam) in vitro preservation medium, in order to make plant grow slowly and healthy. Experiment was done in Molecular Biologi Laboratory of PAU IPB. The experiment was arranged in factorial complete random design, using sweet potato var. Sukuh in order to know the effect of sucrose (40,50,60,70 and 80 g l-1) and agar (7 and 8 g l-1) which were added 1 g l-1 hyponex fertilizer 20-20-20. The experiment was replicated four times. Data were analyzed parametrically and non-parametrically. The result of these experiments showed the suitable conservation media was 1 g l-1 hyponex 20-20-20 + 60 g l-1sucrose + 7 g l-1 agar. Threfore, the media composition MS could produce high green inter nodes number, high root number and more than two green leaf number. This experiment also showed that MS media could be replaced by a cheaper and easily found conservation medium.